The Concept of “the Type of an Art” - Stolovičius, Leonidas (Problemos, 1975)
An attempt is made to relate the distinguishing of the main types of artistic creation to the structure of artistic activity, the graphical model of which the author has built in other publications (“Nature of Aesthetical Value”, “Experience of Building the Model of Artistic Reality”). In the author’s opinion the classification of artistic creation types is based upon the place of one type or another in the system of coordinates of “subject–object” and “individual–society”. Proceeding from this principle of division and having in mind the history of artistic development, it is possible and expedient to distinguish three types of artistic creation: 1) the objective, 2) the subjective-individual, 3) the subjective-social or normative. The objective type is revealed through various realistic methods, the subjective individual type through romantic methods (symbolism and expressionism, including the subjective-social (normative) through classicism. The fine arts are the main sphere of the objective type. In nonfine arts the subjective-individual type of creation many widely manifest itself. Various types of creation present various opportunities for creating artistic value, although not all of the methods are equally artistically productive.